Superconvergent sum rules for the normal reflectivity - Furuya, K.; Zimerman, A. H.; Villani, A. (IOP Publishing, 1977)
Families of superconvergent relations for the normal reflectivity function are given. Sum rules connecting the difference of phases of the reflectivities of two materials are also considered. Finally superconvergence relations and sum rules for magneto-reflectivity in the Faraday and Voigt regimes are also studied.